Effect of graphite addition on impregnated diamond bit properties - Lanlan Xie; Liyi Chen; Xiaolin Huang (Сверхтвердые материалы, 2019)
Graphite was used as a solid lubricant to reduce thermal damage in diamond bit when drilling without coolant. Graphite was added to the bit matrix material to reduce friction coefficient and heat. The influence of content, granularity, and surface metallization of graphite on the mechanical property and dry friction properties of the matrix, as well as the effect of diamond lifetime in the working layer were studied. Results showed that the hardness, bending strength, and friction coefficient of matrix gradually decreased with the increase in graphite concentration.